Heart-brain axis: Association of congenital heart abnormality and brain diseases - Sha, Leihao; Li, Yajiao; Zhang, Yunwu; Tang, Yusha; Li, Baichuan; Chen, Yucheng; Chen, Lei (Frontiers in Cardiovascular Medicine, 2023)
Brain diseases are a major burden on human health worldwide, and little is known about how most brain diseases develop. It is believed that cardiovascular diseases can affect the function of the brain, and many brain diseases are associated with heart dysfunction, which is called the heart-brain axis. Congenital heart abnormalities with anomalous hemodynamics are common treatable cardiovascular diseases. With the development of cardiovascular surgeries and interventions, the long-term survival of patients with congenital heart abnormalities continues to improve. However, physicians have reported that patients with congenital heart abnormalities have an increased risk of brain diseases in adulthood. To understand the complex association between congenital heart abnormalities and brain diseases, the paper reviews relevant clinical literature. Studies have shown that congenital heart abnormalities are associated with most brain diseases, including stroke, migraine, dementia, infection of the central nervous system, epilepsy, white matter lesions, and affective disorders. However, whether surgeries or other interventions could benefit patients with congenital heart abnormalities and brain diseases remains unclear because of limited evidence.